MC3T3-E1 Cells on Titanium Surfaces with Nanometer Smoothness and Fibronectin Immobilization - Tohru Hayakawa; Eiji Yoshida; Yoshitaka Yoshimura; Motohiro Uo; Masao Yoshinari (International Journal of Biomaterials)
The present study was aimed to evaluate the viability and total protein contents of osteoblast-like cells on the titanium surface with different surface mechanical treatment, namely, nanometer smoothing (Ra: approximately 2.0 nm) and sandblasting (Ra: approximately 1.0 μm), and biochemical treatment, namely, with or without fibronectin immobilization. Fibronectin could be easily immobilized by tresyl chloride-activation technique. MC3T3-E1 cells were seeded on the different titanium surfaces. Cell viability was determined by MTT assay. At 1 day of cell culture, there were no significant differences in cell viability among four different titanium surfaces. At 11 days, sandblasted titanium surface with fibronectin immobilization showed the significantly highest cell viability than other titanium surface. No significant differences existed for total protein contents among four different titanium surfaces at 11 days of cell culture. Scanning electron microscopy observation revealed that smoothness of titanium surface produced more spread cell morphologies, but that fibronectin immobilization did not cause any changes of the morphologies of attached cells. Fibronectin immobilization provided greater amount of the number of attached cells and better arrangement of attached cells. In conclusion, the combination of sandblasting and fibronectin immobilization enhanced the cell viability and fibronectin immobilization providing better arrangements of attached cells.